The Socio-educational Theory of the “Invisible Hand” - Lisauskienė, Dovilė; Aleksienė, Vilmantė (Social Welfare: Interdisciplinary Approach, 2023)
The Socio-educational Theory of the “Invisible Hand” is the result of the research using constructivist grounded theory strategy. The socio-educational factors of recreational activities carried out in regional open youth centres/spaces were investigated. The study has included young people with fewer opportunities (YPFO) aged 16–20 and the youth workers. The study started in January and ended on September 2021.In the research data analysis, the recurring word “invisible” was noted, bringing up the image of the “invisible hand”. The metaphor of the “invisible hand” was used to visualize, understand and explain the process of social education through recreation. The constructed grounded theory – the Socio-educational Theory of the “Invisible Hand”, was linked to the economical theory of the Invisible Hand described by the economist A. Smith (1776).It has been revealed that it is a process consisting of visible and invisible sub-processes running simultaneously. The invisible one is not direct or pre-planned. It is a process that can be accidental or conscious, spontaneous or purposeful.
Keywords: socio-education; young people with fewer opportunities; social work; open youth centre; the Invisible Hand theory; constructivist grounded theory